2019
DOI: 10.1021/acs.inorgchem.9b02799
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III) Complexes Bearing a Formal Tetradentate Coordination Chelate: Structural Properties and Phosphorescence Fine-Tuned by Ancillaries

Abstract: Synthesis of the multidentate coordinated chelate N3C–H2, composed of a linked functional pyridyl pyrazole fragment plus a peripheral phenyl and pyridyl unit, was obtained using a multistep protocol. Preparation of Ir­(III) metal complexes bearing a N3C chelate in the tridentate (κ3), tetradentate (κ4), and pentadentate (κ5) modes was executed en route from two nonemissive dimer intermediates [Ir­(κ3-N3CH)­Cl2]2 (1) and [Ir­(κ4-N3C)­Cl]2 (2). Next, a series of mononuclear Ir­(III) complexes with the formulas [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…X-ray structure of one of the two independent molecules of 6b showing 50% thermal ellipsoid probability (hydrogen atoms have been omitted). Selected bond lengths (Å) and angles (degree) for both molecules: Ir(1)−C(1) = 1.993( 9), 1.996 (9), Ir(1)−C(19) = 2.096 (9), 2.118 (9), Ir(1)−C(29) = 2.080 (9), 2.071 (9), Ir(1)−N(1) = 1.984(7), 1.956 (8) Cations of salts 8 and 10 are the result of a hydrogen-transfer reaction at the metal coordination sphere from the aryl substituent of the incoming pyridine ligand to the phenyl unit of the benzyl group of the tetradentate ligand. In addition, a position exchange between the pyridyl and phenyl rings of the 2benzylpyridine moiety takes place; that is, in contrast to the previous complexes of this work, the phenyl substituent of the 2phenylisoquinoline moiety and the phenyl unit of the benzyl group are mutually trans disposed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…X-ray structure of one of the two independent molecules of 6b showing 50% thermal ellipsoid probability (hydrogen atoms have been omitted). Selected bond lengths (Å) and angles (degree) for both molecules: Ir(1)−C(1) = 1.993( 9), 1.996 (9), Ir(1)−C(19) = 2.096 (9), 2.118 (9), Ir(1)−C(29) = 2.080 (9), 2.071 (9), Ir(1)−N(1) = 1.984(7), 1.956 (8) Cations of salts 8 and 10 are the result of a hydrogen-transfer reaction at the metal coordination sphere from the aryl substituent of the incoming pyridine ligand to the phenyl unit of the benzyl group of the tetradentate ligand. In addition, a position exchange between the pyridyl and phenyl rings of the 2benzylpyridine moiety takes place; that is, in contrast to the previous complexes of this work, the phenyl substituent of the 2phenylisoquinoline moiety and the phenyl unit of the benzyl group are mutually trans disposed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This anion uses the free nitrogen atom of the pyrazolate group to generate the green binuclear emitters B . 9 We have recently shown that the ortho -CH bond activation of both phenyl groups of 2-phenyl-6-(1-phenyl-1-(pyridin-2-yl)ethyl)pyridine gives a dianionic C , N , C ′, N ′-tetradentate 6tt′ ligand, which allows the access to blue-green and green iridium(III) emitters, C and D , of classes [6tt′ + 1m + 2m] and [6tt′ + 3b], respectively. 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The new compound was also characterized by Xray diffraction analysis. 6), Ir1-C26 = 2.125( 6), Ir1-C29 = 2.144( 6), Ir1-C30 = 2.137( 6); N2-Ir1-N1 = 81.00 (17).…”
Section: Scheme 1 Synthesis Of 2-phenyl-6-(1-phenyl-1-(pyridin-2-yl)ethyl)pyridinementioning
confidence: 99%